Rib-oriented Thoracoscopic Sympathetic Surgery for Hyperhidrosis: Prospective Long-term Results and Quality of Life. Issue 3 (16th June 2021) - Nachira, Dania; Meacci, Elisa; Congedo, Maria T.; Petracca-Ciavarella, Leonardo; Zanfrini, Edoardo; Iaffaldano, Amedeo; Vita, Maria L.; Chiappetta, Marco; Griffo, Raffaella; Lococo, Filippo; Margaritora, Stefano
Abstract : Background: The optimal thoracoscopic sympathetic surgery for primary palmar and/or axillary hyperhidrosis (PPAH) is still unclear because of lack of uniform technique and qualitative/quantitative scales for definition of results. The aims of this study were to compare long-term outcomes based on the surgical technique and the level of sympathetic trunk interruption by clipping and to assess postoperative compensatory sweating (CS), patients' satisfaction, and quality of life (QoL). Materials and Methods: Between September 2009 and April 2016, 94 patients who underwent 2-stage bilateral thoracoscopic rib-oriented (R) sympathetic clipping were prospectively followed up through the administration of standardized preoperative and postoperative questionnaires. Thirty-four (36.2%) patients underwent single-port transaxillary access instead of the standard two 5-mm incisions. The level of sympathetic clipping for PPAH was R3+4(top and bottom); in patients who complained associated facial or plantar hyperhidrosis R2-bottom and R5-top were clipped, respectively. Seventy-five patients completed bilateral surgery. Results: There were no significant differences between single-port and biportal video-assisted thoracoscopic surgery in terms of operative times and postoperative results. At a mean follow-up of 72 (SD: 26) months, CS was reported in 42 (56%) patients, severe only in 6 (8%). It was higher in the case of R2-bottom clipping ( P =0.03). Thirty-one of 60 (51.6%) patients who had a plantar hyperhidrosis declared an improvement of feet sweating after surgery. Postoperative satisfaction was excellent (86.11% on a 0 to 100 scale) and 95.4% of patients declared an improvement in QoL, which was statistically significant in all evaluated parameters. These results were not related to the level of clipping. Conclusion: Thoracoscopic R3 to R4 clipping appears to be a safe and effective treatment for PPAH. Although postoperative CS was common and higher after R2-bottom clipping, this did not seem to affect patients' satisfaction and improvement in QoL.